The euro imbalances and financial deregulation: A post-Keynesian interpretation of the European debt crisis - Esteban Pérez-Caldentey; Matías Vernengo (Levy Economics Institute of Bard College, 2012)
Conventional wisdom suggests that the European debt crisis, which has thus far led to severe adjustment programs crafted by the European Union and the International Monetary Fund in both Greece and Ireland, was caused by fiscal profligacy on the part of peripheral, or noncore, countries in combination with a welfare state model, and that the role of the common currency - the euro - was at best minimal.This paper aims to show that, contrary to conventional wisdom, the crisis in Europe is the result of an imbalance between core and noncore countries that is inherent in the euro economic model. Underpinned by a process of monetary unification and financial deregulation, core eurozone countries pursued export-led growth policies - or, more specifically, beggar thy neighbor policies - at the expense of mounting disequilibria and debt accumulation in the periphery. This imbalance became unsustainable, and this unsustainability was a causal factor in the global financial crisis of 2007-08. The paper also maintains that the eurozone could avoid cumulative imbalances by adopting John Maynard Keynes's notion of the generalized banking principle (a fundamental principle of his clearing union proposal) as a central element of its monetary integration arrangement.
Keywords: F32; F36; O52; 330; European Union; current account adjustment; financial aspects of economic integration